BIOCHEMICAL AND IMMUNOLOGICAL INTERACTION BETWEEN DIABETES MELLITUS AND PERIODONTAL DISEASES IN ORTHODONTICS INTERAÇÃO BIOQUÍMICA E IMUNOLÓGICA ENTRE A DIABETES MELLITUS E DOENÇAS PERIONDONTAIS NA ORTODONTIA - Fonseca Garcia, Vinicius; Bertagnolli Coutinho, Loyane; Cézar de Oliveira, Mário (Revista da Faculdade de Odontologia da Universidade Federal da Bahia, 2021)
Periodontal disease is complex once it involves disorders that affect the tissues. The main etiologic agent of the periodontium disease is the bacterial plaque and in its most advanced stages there might be loss of the teeth adhesion to the periodontal and the gingiva, with consequent local bone resorption, resulting in tooth loss. Diabetes mellitus is one of the most common chronic diseases in most countries and it is increasing in number and relevance. In 2019 was estimated that 463 million adults suffered from diabetes mellitus, a metabolic disorder known as being associated to various systemic diseases, as well as being associated with many problems in the oral areas. Studies have shown that diabetes, if untreated, can lead to the development of periodontal diseases. Several mechanisms have been suggested to explain the increased susceptibility to periodontal diseases, including changes in host response, subgingival microflora, gingival crevicular fluid and inheritance patterns. Multiple pathophysiological mechanisms are also associated with increased alveolar bone loss found in diabetic patients. The bidirectional inter-relationship between diabetes mellitus and periodontal diseases typifies a classic example of how a systemic disease can predispose to an oral infection and of how it can exacerbate a systemic condition. A doença periodontal é complexa, pois envolve distúrbios que afetam os tecidos. O principal agente etiológico da doença periodontal é a placa bacteriana e em seus estágios mais avançados pode haver perda da adesão dos dentes ao periodonto e gengiva, com consequente reabsorção óssea local, resultando em perda dentária. O diabetes mellitus é uma das doenças crônicas mais comuns na maioria dos países e está aumentando em número e relevância. Em 2019 foi estimado que 463 milhões de adultos sofreu com a diabetes mellitus, um distúrbio metabólico conhecido por estar associado a várias doenças sistêmicas, além de estar associado a diversos problemas nas áreas bucais. Estudos têm demonstrado que o diabetes, se não for tratado, pode levar ao desenvolvimento de doenças periodontais. Vários mecanismos têm sido sugeridos para explicar o aumento da suscetibilidade às doenças periodontais, incluindo mudanças na resposta do hospedeiro, microflora subgengival, fluido gengival e padrões de herança. Múltiplos mecanismos fisiopatológicos também estão associados à perda óssea alveolar aumentada encontrada em pacientes diabéticos. A inter-relação bidirecional entre diabetes mellitus e doenças periodontais tipifica um exemplo clássico de como uma doença sistêmica pode predispor a uma infecção oral e como pode exacerbar uma condição sistêmica.